Implementation of Principal’s Academic Supervision at MTs Negeri 2 Palembang - Srimulyani, Srimulyani; Fitria, Happy; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2023)
This research was conducted to provide an in-depth description of the implementation of supervision organized by the PrincipaI of MTs Negeri 2 Palembang together with the supervisor team. The method used in this research is descriptive quantitative. The result achieved from the research carried out is that the implementation of supervision has been carried out weII at MTs Negeri 2 Palembang, as evidenced by the stages or procedures carried out in a structured or systematic manner. The implementation of supervision has been scheduled as stated in the annual program of MTs Negeri 2 Palembang. Therefore, every process of the implementation of supervision has been able to reach the things needed to improve the quality of education. The supervision implemented at MTs Negeri 2 Palembang has a good impact on the implementation of education, as stated by the teachers that it is important to continue to carry out supervision so that there is supervision and control in every running process. The implementation of supervision also provides benefits for teachers to improve their professionalism as professional educators.